The big red one [videorecording (DVD)] - Fuller, Samuel, 1912-1997; Fuller, Samuel, 1912-1997; Marvin, Lee; Hamill, Mark; Carradine, Robert, 1954- (Warner Home Video, 2005)
Named for the insignia of the First Infantry Division, this World War II combat film follows a handful of young GIs and their sergeant as they battle their way from North Africa through Sicily, Omaha Beach and Belgium to the ultimate horror of the concentration camp at Falkenau, Czechoslovakia.